Red cell quinine concentrations in falciparum malaria. - White, N; Looareesuwan, S; Silamut, K (1983)
Red cell concentrations of quinine were measured in cerebral malaria and in uncomplicated falciparum malaria both in the acute stage and 1 month after recovery. Red cell quinine elimination half times were significantly shorter than the corresponding plasma half times in cerebral malaria and convalescent uncomplicated cases (P less than 0.001), but not in acute uncomplicated cases (P = 0.12). The ratio of red cell:plasma concentration fell progressively from the 2nd day (0.49) to the 6th day (0.26) of treatment. On admission this ratio was positively correlated with the blood parasite count (P = 0.02). Red cell quinine concentration may be relevant to the assessment of drug resistance, and to the design of treatment regimens.